Taenia Solium Sneezed out from Nose by an Asymptomatic Child - Pant, Narayan Dutt; Sharma, Manisha; Neupane, Sanjeev (Journal of Nepal Health Research Council, 2017)
Taenia solium is an intestinal parasite and may be excreted in feces in infected patients but our case is unique, as an asymptomatic child sneezed out the proglottids of the parasite from his nose. After the full course of antihelminthic drug the patient excreted a whole worm in his stool.Keywords: Antihelminthic drug; asymptomatic; Taenia solium; taeniasis.